Papillon [videorecording (DVD)] - Hunnam, Charlie, 1980-; Malek, Rami; Wageningen, Yorick van, 1964-; Charrière, Henri, 1906-1973; Charrière, Henri, 1906-1973 (Universal Pictures Home Entertainment, 2018)
The epic story of Henri Charrière, a safecracker from the Parisian underworld who is framed for murder and condemned to life in the notorious penal colony on Devil's Island. Determined to regain his freedom, Papillon forms an unlikely alliance with convicted counterfeiter Louis Dega, who, in exchange for protection, agrees to finance Papillon's escape.